2021
DOI: 10.1002/1878-0261.13103
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1‐induced T cell exhaustion is controlled by a Drp1‐dependent mechanism

Abstract: Programmed cell death‐1 (PD‐1) signaling downregulates the T‐cell response, promoting an exhausted state in tumor‐infiltrating T cells, through mostly unveiled molecular mechanisms. Dynamin‐related protein‐1 (Drp1)‐dependent mitochondrial fission plays a crucial role in sustaining T‐cell motility, proliferation, survival, and glycolytic engagement. Interestingly, such processes are exactly those inhibited by PD‐1 in tumor‐infiltrating T cells. Here, we show that PD‐1 pos CD8 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In addition, the CCL5 chemokine has been reported to increase glucose uptake, glycolysis, and ATP production in T cells to meet the increased energy demand during cell migration [ 84 ], presumably by upregulating mTOR, which is also required to promote the expression of chemotaxis-related proteins. Similarly, stimulation of T cells with either CXCL12 or CCL19/21 chemokine activates ERK1/2 and the mitochondrial pro-fission protein Drp1 [ 85 , 86 ], two molecules known to sustain glycolysis in T cells [ 86 , 87 ]. Moreover, glycolysis promotes cell migration of regulatory T cells, too [ 88 ].…”
Section: Metabolism and T-cell Migration Within Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the CCL5 chemokine has been reported to increase glucose uptake, glycolysis, and ATP production in T cells to meet the increased energy demand during cell migration [ 84 ], presumably by upregulating mTOR, which is also required to promote the expression of chemotaxis-related proteins. Similarly, stimulation of T cells with either CXCL12 or CCL19/21 chemokine activates ERK1/2 and the mitochondrial pro-fission protein Drp1 [ 85 , 86 ], two molecules known to sustain glycolysis in T cells [ 86 , 87 ]. Moreover, glycolysis promotes cell migration of regulatory T cells, too [ 88 ].…”
Section: Metabolism and T-cell Migration Within Tumorsmentioning
confidence: 99%
“…Indeed, PD-1 engagement on T cell surface during activation can inhibit both the PI3K/Akt/mTOR and MAPK/ERK signaling pathways, both required for an efficient glycolytic engagement in T cells [ 103 , 104 ]. PD-1 has been also reported ( i ) to inhibit the activation of the mitochondrial pro-fission protein Drp1 [ 85 ], which is required for T cell motility [ 86 ], and ( ii ) to promote disassembly of the mitochondrial cristae [ 102 ], which are required for OXPHOS-dependent ATP generation. Similarly, CTLA-4 engagement on T cell surface dampens the activation of PI3K/Akt/mTOR [ 105 ], and therefore reduces glycolysis.…”
Section: Metabolism and T-cell Migration Within Tumorsmentioning
confidence: 99%
“…Previous studies have shown that PD-1 can inhibit the proliferation and migration of T cells ( 76 , 77 ). Simula and colleagues used a mouse tumor model to explore whether PD-1 regulates these processes by affecting Drp1 ( 78 ). Their study demonstrated that the PD-1 signal inhibits the division of mitochondria in T cells by inhibiting the phosphorylation of Ser616 sites, and this inhibition is achieved through the ERK and mTOR pathways ( 76 , 78 , 79 ) ( Figure 2 ).…”
Section: Drp1-mediated Mitochondrial Division and T Cell Exhaustion I...mentioning
confidence: 99%
“…Simula and colleagues used a mouse tumor model to explore whether PD-1 regulates these processes by affecting Drp1 ( 78 ). Their study demonstrated that the PD-1 signal inhibits the division of mitochondria in T cells by inhibiting the phosphorylation of Ser616 sites, and this inhibition is achieved through the ERK and mTOR pathways ( 76 , 78 , 79 ) ( Figure 2 ). Compared with thymocyte Drp1-knockout mice, PD-1 inhibitors significantly enhanced the anti-tumor effect of wild-type mice, and this difference was related to the phosphorylation level of Drp1 in T cells ( 78 ).…”
Section: Drp1-mediated Mitochondrial Division and T Cell Exhaustion I...mentioning
confidence: 99%
See 1 more Smart Citation